Female Sexual Dysfunction in Patients with Major Depressive Disorder (MDD) Treated with Selective Serotonin Reuptake Inhibitor (SSRI) and Its Association with Serotonin 2A—1438 G/A Single Nucleotide Polymorphisms. (1st April 2014) - Masiran, Ruziana; Sidi, Hatta; Mohamed, Zahurin; Mohd Nazree, Nur Elia; Nik Jaafar, Nik Ruzyanei; Midin, Marhani; Das, Srijit; Mohamed Saini, Suriati
Abstract: Introduction: Selective serotonin reuptake inhibitors (SSRIs) are known for their sexual side effects. Different SSRIs may affect different areas of sexual function at different rates. Aims: The study aimed to determine the prevalence of female sexual dysfunction (FSD), its clinical correlates, and association with 5HT2A (rs6311) single nucleotide polymorphisms (SNPs) in patients with major depressive disorder (MDD) who were on SSRI therapy. Methods: This was a cross‐sectional study on 95 female outpatients with MDD treated with SSRI. The patients were in remission as determined by Montgomery–Asberg Depression Rating Scale. Genomic DNA was isolated from buccal swabs and samples were processed using a real time polymerase chain reaction. Main Outcome Measures: The presence or absence of FSD as measured by the Malay Version of Female Sexual Function Index and 5HT2A‐1438 G/A (rs6311) SNP. Results: The overall prevalence of FSD was 32.6%. After controlling for age, number of children, education level, total monthly income, SSRI types, and SSRI dosing, being employed significantly enhanced FSD by 4.5 times (odds ratio [OR] = 4.51; 95% confidence interval [CI] 1.00, 20.30; P = 0.05). Those having marital problems were 6.7 times more likely to have FSD (OR = 6.67; 95% CI 1.57, 28.34). 5HT2A‐1438 G/A (rs6311) SNP was not significantly associated with FSD. Conclusion: There was no significant association between FSD and the 5HT2A (rs6311) SNP in patients with MDD on SSRI therapy. Employment status and marital state were significantly associated with FSD among these patients.